Expanding Housing Finance in Uganda : Task 2. Study to Examine the Use of Retail Funds for Mortgage Lending - Hanouch, Michel; Ketley, Richard; Kramer, Jessica; Wiese, Christo (World Bank, Washington, DC, 2013)
The objective of the First Initiative Project in Uganda is to expand the access of households to housing finance, especially modest and lower income households, by introducing new and innovative housing loan products, by introducing innovative loan products combined with affordable housing designs. The project has delivered two studies to the Bank of Uganda: i) a study addressing the financial and banking sector context for housing finance, liquidity and liquidity management, and the resultant potential for use of retail funds for mortgage lending; and ii) a feasibility study for housing finance pilots targeted at modest and lower income households, seeking to introduce innovative loan products combined with lower cost house design in a planned urban setting. This paper, business and sustainability plan for affordable housing finance pilot projects, provides supporting technical detail for the feasibility study for design of pilot projects for modest and lower income households, including the need for more liquidity for lenders involved in lending to lower income households. Two types of pilot projects have been developed: one for starter homes for modest income households and one for an incrementally built home for low-modest income households. The recommended loan products include a down-market or, mini-mortgage, for the starter home and microfinance for housing for the lower income group. The paper: (i) outlines technical details regarding house design and loan product specifications; (ii) recommends the technical assistance and regulatory changes deemed necessary to implement successful pilot; and (iii) provides a brief commentary on actions that would assist such pilots reach sustainability and scale.